2014
DOI: 10.1038/srep06266
|View full text |Cite
|
Sign up to set email alerts
|

Tuning calcite morphology and growth acceleration by a rational design of highly stable protein-mimetics

Abstract: In nature, proteins play a significant role in biomineral formation. One of the ultimate goals of bioinspired materials science is to develop highly stable synthetic molecules that mimic the function of these natural proteins by controlling crystal formation. Here, we demonstrate that both the morphology and the degree of acceleration or inhibition observed during growth of calcite in the presence of peptoids can be rationally tuned by balancing the electrostatic and hydrophobic interactions, with hydrophobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 33 publications
2
86
0
Order By: Relevance
“…The non-ionic amino acids apparently have little effect on protein-crystal interactions beyond dilution of the effect of the strongly interacting anionic groups or spatial separation of charged groups along the primary sequence, though one publication showed the hydrogen bonding, non-ionic amino acids like serine could enhance surface interactions compared to other non-ionic amino acids [83] . Also, hydrophobic interactions at crystal surfaces have been suggested to play an important role in growth acceleration based on data in calcite (calcium carbonate) [84] . While modeling the complexity of the mixture of hundreds of urinary proteins is beyond our current level of understanding of protein-crystal interactions, numerous studies have revealed that the mixture of proteins from normal individuals inhibits growth and aggregation of COM crystals, consistent with net anionic character of the protein mixtures [85] .…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…The non-ionic amino acids apparently have little effect on protein-crystal interactions beyond dilution of the effect of the strongly interacting anionic groups or spatial separation of charged groups along the primary sequence, though one publication showed the hydrogen bonding, non-ionic amino acids like serine could enhance surface interactions compared to other non-ionic amino acids [83] . Also, hydrophobic interactions at crystal surfaces have been suggested to play an important role in growth acceleration based on data in calcite (calcium carbonate) [84] . While modeling the complexity of the mixture of hundreds of urinary proteins is beyond our current level of understanding of protein-crystal interactions, numerous studies have revealed that the mixture of proteins from normal individuals inhibits growth and aggregation of COM crystals, consistent with net anionic character of the protein mixtures [85] .…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…Peptoids also exhibit potent biological functionalities and are biocompatible 27–29 . In a recent study 3031 , dramatic modifications of CaCO 3 crystal growth rate and morphology by peptoids highlighted the potential of using these polymers for biomimetic approaches to controlling mineralization and remineralization. Here, we showed peptoids’ potency to guide and modulate HAP mineralization on collagen substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of simple, low-energy pathways for the growth of highly desirable and unstable polymorphs with vital industrial and biological applications is particularly important. [1][2][3][4][5][6][7][8][9][10] Numerous examples of high level control over polymorphism have been established for both organic [1][2][3] and inorganic [4][5][6][7][8] crystal systems. In particular, the calcium carbonate crystal system has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the calcium carbonate crystal system has been extensively studied. [4][5][6][7]9,10 Crystal growth additives such as natural proteinmimics 4,10 and polymers [5][6][7] are commonly used to achieve the growth of the metastable polymorphs, vaterite and aragonite, at much lower temperatures than otherwise possible.…”
Section: Introductionmentioning
confidence: 99%